2005
DOI: 10.1115/1.1992521
|View full text |Cite
|
Sign up to set email alerts
|

3-D Numerical Simulation of Blood Flow Through Models of the Human Aorta

Abstract: A Spiral Computerized Tomography (CT) scan of the aorta were obtained from a single subject and three model variations were examined. Computational fluid dynamics modeling of all three models showed variations in the velocity contours along the aortic arch with differences in the boundary layer growth and recirculation regions. Further down-stream, all three models showed very similar velocity profiles during maximum velocity with differences occurring in the decelerating part of the pulse. Flow patterns obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
84
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 29 publications
7
84
1
Order By: Relevance
“…Aortic arch hemodynamics has been investigated using computational fluid dynamics (CFD) in the normal mature adult-scale of human aorta [22][23][24] and in mouse aortic models of atherosclerosis [25][26][27]. Relevant to patients with congenital heart disease, a patient specific neonatal aortic arch configuration [28] and an in vitro experimental and computational study of normal and abnormal embryonic aortic arch hemodynamics at late gestation [29] was published by our group.…”
Section: Introductionmentioning
confidence: 99%
“…Aortic arch hemodynamics has been investigated using computational fluid dynamics (CFD) in the normal mature adult-scale of human aorta [22][23][24] and in mouse aortic models of atherosclerosis [25][26][27]. Relevant to patients with congenital heart disease, a patient specific neonatal aortic arch configuration [28] and an in vitro experimental and computational study of normal and abnormal embryonic aortic arch hemodynamics at late gestation [29] was published by our group.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that circumferential components contributed significantly to the hemodynamic effects on the walls of the aortic arch. Gao et al conducted an analysis of the pulsatile blood flow between the layers of the aortic arch [14]. They found that the circumferential tension of the arterial wall is directly related to arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes it is difficult to obtain experimental results from humans for ethical reasons, particularly when managing aortic surgery. For this reason, the computational fluid dynamic (CFD) method has been increasingly used to identify the best treatment strategy for humans, and is a useful tool for simulating the blood flow of the human aorta [8][9][10][11][12][13][14]. The CFD method can provide 3D numerical simulations of blood flow through an aortic model, providing for the identification of pathological mechanisms or the development of design changes in devices used in the aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The arterial wall was considered to be rigid and the no-slip condition was applied. To simulate a cardiac cycle, a time-dependent flat (plug) velocity profile used together with a pulsatile waveform was applied as inlet boundary condition (Dabagh et al, 2015;Morris et al, 2005;Shahcheraghi et al, 2002). This physiologically representative pulsatile waveform is…”
Section: Boundary Conditionsmentioning
confidence: 99%